Effects of Cocaine on Human Glial-Derived Extracellular Vesicles - Kumar, Sanjay; Matthews, Qiana L.; Sims, Brian (Frontiers in Cell and Developmental Biology, 2021)
Background Microglia are important myeloid cells present in the brain parenchyma that serve a surveillance function in the central nervous system. Microglial cell activation results in neuroinflammation that, when prolonged, can disrupt immune homeostasis and neurogenesis. Activated microglia-derived extracellular vesicles (EVs) may be involved in the propagation of inflammatory responses and modulation of cell-to-cell communication. However, a complete understanding of how EVs are regulated by drugs of abuse, such as cocaine, is still lacking. Findings Cocaine exposure reduced human microglial cell (HMC3) viability, decreased expression of CD63 and dectin-1 in HMC3-derived EVs, and increased expression of the apoptotic marker histone H2A.x in HMC3-derived EVs. Conclusion Cocaine impacts HMC3 cell viability and specific EV protein expression, which could disrupt cellular signaling and cell-to-cell communication.